Effectiveness of lactic and acetic acids on the growth of Listeria monocytogenes and Bacillus cereus in primo sale fresh cheese. (November 2021) - Tirloni, Erica; Bernardi, Cristian; Celandroni, Francesco; Ghelardi, Emilia; Stella, Simone
Abstract: In this study Brain Heart Infusion broth inoculated with Listeria monocytogenes with a concentration of acetic acid of 24.98 mM or a concentration of 44.40 mM of lactic acid did not determine the increase in absorbance in 7 days. A concentration of acetic acid of 24.98 mM and a concentration of 22.20 mM of lactic acid were effective against Bacillus cereus growth. Then, challenge tests on primo sale cheese were conducted to establish if these concentrations were efficient when applied to cheese. After inoculum with the pathogens (2 log CFU g −1 ), cheese was dipped with acetic and lactic acid solutions. In a first trial, L. monocytogenes inoculated, showed the absence of significant differences in growth at 4 °C among the treated series (Ac1: acetic acid - 49.96 mM; Ac2: 24.98 mM; Lac1: lactic acid – 88.80 mM; Lac2: 44.40 mM) if compared to Control (CTRL) series (dipped with sterile water). At 8 °C, a significantly lower growth in Ac1 samples if compared to control ones and to all the treated series was observed (P < 0.05). The trial conducted inoculating B. cereus did not show any difference at 15 °C among samples treated with organic acids if compared to control series. Highlights: BHI with acetic acid at 24.98 mM did not show to favour B. cereus and L. monocytogenes growth. BHI with lactic acid at 44.40 and 22.20 mM did not favour L. monocytogenes and B. cereus growth. Challenge tests with bacteria inoculated on cheese were used to evaluate the efficacy of the acids. In samples treated with 88.8 mM of acetic acid L. monocytogenes grew slower at 8 °C. B. cereus did not show any difference at 15 °C among samples treated with organic acids.